ChemInform Abstract: Ta12/Ta16 Cluster‐Containing Polytantalotungstates with Remarkable Photocatalytic H2 Evolution Activity. Issue 14 (20th March 2013) - Li, Shujun; Liu, Shumei; Liu, Shuxia; Liu, Yiwei; Tang, Qun; Shi, Zhan; Ouyang, Shuxin; Ye, Jinhua
Abstract Compounds (III) and (VII) are tris‐(peroxotantalum)‐substituted Dawson‐ and Keggin‐type derivatives, whereas (IV) and (VIII) are tetrameric oligomers containing an unprecedented Ta12 and Ta16 core, respectively.